TEKNOLOGI PANEL SURYA UNTUK PENGOLAHAN LIMBAH SISA PENYULINGAN MINYAK KAYU PUTIH - Rahmat, Saepul; Hendi Purnata; Novita Asma Ilahi; Afrizal Abdi Musyafiq (Jurnal Berdaya Mandiri, 2023)
Ujungmanik Village, Kawunganten District, Cilacap Regency, which is in the Segara Anakan Cilacap area, has natural resources, especially eucalyptus plants, which have the potential to develop the economy of the village community. The biggest problem faced by LMDH Dadi Makmur as a unit that manages the eucalyptus oil business is that after the production of eucalyptus oil distillation, it will produce residual waste from cajuput oil twigs and leaves with quite a large volume and only be left piled up around the yard where the distillery is, causing area storage of essential oil raw materials is narrow and also takes a long time to become organic fertilizer. The innovation offered through this community service activity is implementing a briquette printing machine from eucalyptus oil refining waste which is energy efficient and based on solar panels. The results of the dedication show that the eucalyptus oil waste processing activity in addition to reducing environmental pollution also produces biomass briquettes that can be utilized by the residents of Ujungmanik Village as a leading economic product of Ujungmanik Village.  Keyword: Cajuput oil, briquette, solar panels